التطور العمراني بإقليم توات خلال العصر الوسيط - دويم,مسعود; قدوده.معمر; العبيدي,فيصل (University of Eloued جامعة الوادي, 2024)
مذكرة مكملة لنيل شهادة الماستر بعنوان : التطور العمراني بإقليم توات خلال العصر الوسيط، تتكون من مقدمة وفصل تمهيدي يحتوي على بعض التعريفات مثل الفقارة، القصبة، القصر وفصل أول بعنوان : البيئة الجغرافية والتاريخية لإقليم توات، ذكرنا فيه أصل التسمية وأهم الروايات عن أصل التسمية، والموقع الفلكي والجغرافي للإقليم، وجهاته الثلاث : - توات الوسطى - تينكورارين - تيديكلت، وأهم قصور كل جهة. فصل ثاني بعنوان: العمارة الدينية حيث تطرقنا فيه لأهم المعالم الدينية في الإقليم تلك الفترة منها الزوايا والمساجد والأضرحة، مع تقديم أمثلة عن كل عنصر منها. فصل ثالث معنون بـ: العمارة المدنية والعسكرية، حيث أشرنا في المبحث الأول للأسواق وأهم الطرق التجارية، أما المبحث الثاني تطرقنا فيه إلى أهم الهياكل العسكرية من تحصينات ميدانية وأخرى ثابتة. وختمنا المذكرة باستعراض اهم النتائج المتوصل إليها. ومجموعة من الملاحق وقائمة للمصادر والمراجع المعتمد عليها وفهرس المذكرة. Supplementary Memorandum for Obtaining a Master's Degree entitled: Urban Development in the Touat Region during the Medieval Period.** It consists of an introduction and a preliminary chapter containing some definitions such as foggara, kasbah, and qasr. The first chapter is titled: The Geographical and Historical Environment of the Touat Region, in which we mentioned the origin of the name and the most important stories about the origin of the name, the astronomical and geographical location of the region, and its three parts: - Central Touat - Tinkourarine - Tidikelt, and the most important qasrs in each part. The second chapter is titled: Religious Architecture, in which we discussed the most important religious landmarks in the region during that period, including zawiyas, mosques, and shrines, with examples of each element. The third chapter is titled: Civil and Military Architecture, where we pointed out in the first section the markets and the most important trade routes. The second section discussed the most important military structures, including field fortifications and permanent fortifications. The memorandum concludes by reviewing the most important results achieved and includes a set of appendices, a list of sources and references used, and an index of the memorandum.
Keywords: العمارة; توات; التحصينات الميدانية; الزوايا; تينكورارين; تيديكلت; TECHNOLOGY::Civil engineering and architecture; Touat; Tinkourarine; Tidikelt